Efficiency examination of antihypertensives fixed combination in patientes who had been on antihypertensive monotherapy - Nikolić, Nemanja; Kostic, Tomislav; Marinkovic, Marija; Golubovic, Mlađan; Stojanovic, Tamara; Manojlovic, Milena; Petkovic, Igor (Acta medicae Medianae, 2021)
Arterial hypertension is the condition where the blood pressure is higher than 140/90 mmHg. Along with i'ts complication,s it is  the leading factor for cardiovascular mortality. Artherial hypertension can be systolic, diastolic and combined. Diagnosis of artherial hypertension can not be set up based on the single measurement, it is already necessary to make measurements in different situations and environments.The aim of this study is antihypertensives fixed combination efficiency monitoring in patients with low or moderate hypertension in which antihypertensive monotherapy has not achieved adequate values of blood pressure. In this examination we have analyzed data of 395 patients, aged between 65 to80 years, with first and second grade  hypertension, who did not achieved adequate value of blood pressure with monotherapy. During 4 months of examination, patients were attended by 3 visits whereby their TA values were measured, and each of them has received antihypertensives fixed combination. The data obtained were processed by appropriate statistical analyzes. On the third visit to the doctor 69,8% patients have achieved blood pressure target value, and the blood pressure decreased for 16,6 /12,3% (р=0,000). Nonivasive 24h Holter monitoring showed significantly less oscillation in blood pressure values throughout the day, and also the patients were in a much smaller percentage forgotten to take therapy. During this study it was proved the efficiency of antihypertensive fixed combination considering that in a considerable number of patients blood pressure has been brought to the target values, there were no unwanted side effects, the patients  rarely forgot  to take the medicine, and there were significantly less oscilation in blood pressure on Holter monitoring.
Keywords: arterial hypertension, antihypertensives fixed combination,antihypertensive monotherapy